A Review of International Risk Sharing for Policy Analysis - Pilar Poncela; Michela Nardo; Filippo M. Pericoli (East Asian Economic Review (EAER), 2019)
This paper offers a comprehensive view of international risk sharing and of related policy issues from the perspective of the European Union. The traditional analyses contemplate three risk-sharing channels: the capital markets channel (through cross border portfolio investments), international transfers and the credit markets channel (via savings). Comparative analyses reveal that, on average, about 80% of the shock remains unsmoothed in Europe while only about 18% of the shock is transmitted to consumers within the US. From aggregated figures, there is space for improving, particularly, the cross-border investments channel in Europe. In this sense, the completion of the Banking and Capital Markets Union are expected to boost risk sharing across European member states. We also review new additional issues usually not contemplated by the traditional literature as depreciation, migration and the role of sovereigns and two new additional channels recently considered in the literature: government consumption and the real exchange rate. Finally, we also examine recent analysis related to the geographic distribution of risk sharing.
Keywords: F01; F40; F45; 330; International Risk Sharing; Monetary Union; Policy Analysis; Consumption Smoothing; Cross-border Investments